Individual investors’ behavior in decision making on securities investment in Indonesia Stock Exchange (ISE) - Dihin Septyanto; MF. Arrozi Adhikara (Journal of Economics, Business, and Accountancy Ventura, 2014)
This study tests the benefits of investment in financial information, sophisticated and rational attitude, and risk preferences of investors on utility maximization in investment decision-making process. This study is clear causality with the survey on the opinions, attitudes, experiences, or characteristics of the study individual subjects. Time dimension is one shot study on 182 investors. Data analysis was done using Structural Equation Modeling (SEM) with AMOS program. It shows that the benefits of financial information does not affect the investment intentions; Subjective norms positively affect the investment intentions; Subjective norms have positiveinfluence on belief revision; usefulness of accounting information has  positive influence on the perception of systemic risk; positive belief revision affects investment intentions, and systematic risk perception negatively affect the investment intentions. They become sophisticated investors and irrational because it does not utilize the information in the financial statements of the stock investment decisions. They risk averter because when they have a positive attitude towards risk stocks, investors avoid acting in investment intentions.